Effect of some plant extract for the Biological aspect of black bean aphid Aphis fabae Scopoli (Homoptera : Aphididae) - Henaa Rehman Lefta (Al-Qadisiyah Journal of Pure Science, 2018)
This research was conducted to evaluate the efficiency of watery extract of plant Myrtus communis , Eucalyptus camaldulensis  and Lawsonia inermis tested laboratory against the different stages of the insect of Black bean aphid A.fabae .The results showed that the watery extract of M. communis the highest effect , the first nymph instars have showed highest mortality rate reached 90% and 96.66% when treated with 15 mg /ml concentration after 24 and 48 hours of treatment , followed by watery extract of E. camaldulensis 80% and 90% and L. inermis  70% and 76.66% at 15 concentration after 24 and 48 hours of treatment .Treatment with hieghst concentration caused high adult mortality i.e. 80% , 70%  and 56.66% to extract of M. communis , E. camaldulensis and L. inermis of the mentioned at 48 hours of treatment .